Scheduling to Minimize the Number of Late Jobs When Set-Up and Processing Times are Uncertain - Balut, Stephen J. (Management Science, 1973)
The n job, one-machine scheduling problem is considered where set-up and processing times are random and the objective is to minimize the number of late jobs. In the deterministic case, Moore's algorithm is known to produce an optimal schedule. A chance-constrained formulation of the nondeterministic problem is derived in which a job is processed if the probability that it will be completed prior to its due date is greater than a specified level. A deterministic equivalent problem is achieved to which application of a modification of Moore's algorithm is proven to produce an optimal schedule.